Molecular modeling of 7-hydroxy-3-(1-hydroxyethyl)-5-methoxy-3,4-dimenthylisobenzofuran-1(3H)-one and 4, 8-dihydroxy-6-methoxy-3,4,5-trimethylisochroman-1-one using MOPAC software - Tayone, Wilanfranco C. (Davao Research Journal: the official R & D Publication of Davao Oriental State College of Science and Technology, 2013)
A benzofuranone type of compound known as 7-hydroxy-3(1-hydroxyethyl)-5-methoxy-3,4-dimenthylisobenzofuran-1(3H)-one (1) and 4,8-dihydroxy-6-methoxy-3,4,5-trimethylisochroman-1-one (2) were studied for the molecular modeling using MOPAC. Compound 1 was originally isolated from the fungus Leptosphaeria sp. KTC 727. INitial Nuclear Magnetic Resonance (NMR) analyses using 1H,13C, Correlation Spectroscopy (COSY), Heteronuclear Multiple Quantum Coherence (HMQC), Heteronuclear Multiple Bond Coherence (HMBC) and Mass Spectrometry (MS) suggested 1 and 2 as the candidate planar structures. Succeeding chemical experiments confirmed it to be 1 and not 2. This study provided new confirmatory evidence about the exclusion of 2 as possible candidate compound via theoretical computation approach using MOPAC software.